MENIMBANG KEBIJAKAN TERHADAP NARAPIDANA PADA MASA PANDEMI - Endar Susilo (Qistie Jurnal Ilmu Hukum, 2020)
The policy taken by the government towards prisoners during the corona virus disease-19 (covid-19) pandemic, namely assimilation and integration of prisoners received a lot of attention. By using a normative juridical approach, this paper seeks to find out how the legal basis of policy towards prisoners during a pandemic and how policy considerations towards prisoners during a pandemic. This research resulted in 2 things, firstly the Ministry of Law and Human Rights issued several rules regarding the provision of assimilation and the right of integration for prisoners and children in the context of preventing and controlling the spread of Covid-19. Second, several factors that are considered in policy making are infrastructure, human resources, and operational budgets